1996
DOI: 10.1085/jgp.107.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Block of single L-type Ca2+ channels in skeletal muscle fibers by aminoglycoside antibiotics.

Abstract: ABSTRACX The activity of single L-type Ca 2+ channels was recorded from cell-attached patches on acutely isolated skeletal muscle fibers from the mouse. The experiments were concerned with the mechanism by which aminoglycoside antibiotics inhibit ion flow through the channel. Aminoglycosides produced discrete fluctuations in the single-channel current when added to the external solution. The blocking kinetics could be described as a simple bimolecular reaction between an aminoglycoside molecule and the open ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
(49 reference statements)
2
35
0
1
Order By: Relevance
“…Table 2 summarizes the parameters associated with intracellular block by neamine and sisomycin AGs as low affinity pore blockers of μ1 channels In previous studies the estimated affinities of AG antibiotics for N-type and P/Q-type Ca 2+ channels, as measured by competitive inhibition of radiolabeled toxin binding, were in the nanomolar to micromolar range [16,22]. In contrast, the estimated K d values of AGs, as measured from current blockade under voltage-clamp conditions, were typically higher and ranged from hundreds of micromoles for P/Q-type Ca 2+ channels [22] to millimoles for L-type Ca 2+ channels [14,18]. We found that the estimated affinity of the more potent AGs (neomycin and sisomycin) for μ1 channels was similar to the affinity of some AGs for L-type Ca 2+ channels because the 0 voltage K d values estimated from the Woodhull model (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Table 2 summarizes the parameters associated with intracellular block by neamine and sisomycin AGs as low affinity pore blockers of μ1 channels In previous studies the estimated affinities of AG antibiotics for N-type and P/Q-type Ca 2+ channels, as measured by competitive inhibition of radiolabeled toxin binding, were in the nanomolar to micromolar range [16,22]. In contrast, the estimated K d values of AGs, as measured from current blockade under voltage-clamp conditions, were typically higher and ranged from hundreds of micromoles for P/Q-type Ca 2+ channels [22] to millimoles for L-type Ca 2+ channels [14,18]. We found that the estimated affinity of the more potent AGs (neomycin and sisomycin) for μ1 channels was similar to the affinity of some AGs for L-type Ca 2+ channels because the 0 voltage K d values estimated from the Woodhull model (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Although neuronal subtypes of sodium channels could be more susceptible to blockade by AGs at concentrations of therapeutic interest, this is a remote possibility given the very low affinity of AGs for skeletal muscle channels. Previous studies have suggested that AG inhibition of Ca 2+ -activated K + current [21] and L-type Ca 2+ current [14] generally depended upon the number of amine groups on the AG. In contrast, AG inhibition of mechanosensitive channels from mouse skeletal muscle [29] and P/Q-type Ca 2+ channels [22] seemed to be more complex because there was no direct relationship between the number of amine moieties on the AG and the potency of block.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Benzalkonium chloride completely displaced radioligand binding to Nand P/Q-type VDCCs at 10 µM concentration and displayed a biphasic effect on the specific binding of [ 3 H]nitrendipine, with a very significant increase in binding when the concentration of benzalkonium chloride is as described to occur in numerous topical ocular preparations (≥200 µM or approximately 0.007%). The ability of benzalkonium chloride to interact with VDDCs is probably due to its quaternary ammonium structure: drugs sharing this structure, for example aminoglycoside antibiotics [20,41], are known to interact with VDDCs. Corneal epithelial cells may express L-type VDDCs [50] and hence an interaction of topical benzalkonium chloride with these channels could affect the physiology of the corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…A mutação ∆F508 interfere com o "folding" normal da proteína, com sua glicosilação e com o funcionamento do canal na membrana apical, interferindo na probabilidade de abertura do canal (Po) (31,33) .…”
Section: Cftr Na Fibrose Císticaunclassified